Mast Cells as Important Regulators in Autoimmunity and Cancer Development - Noto, Christine N.; Hoft, Stella G.; DiPaolo, Richard J. (Frontiers in Cell and Developmental Biology, 2021)
Mast cells are an essential part of the innate immune system and are best known as important modulators of allergic and anaphylactic immune responses. However, mast cells also play important roles in regulating autoimmune diseases including rheumatoid arthritis, type 1 diabetes, and multiple sclerosis. Importantly, chronic inflammation and autoimmunity are linked to the development of specific cancers. Inflammatory mediators released from activated mast cells regulate immune responses and promote vascular permeability and the recruitment of immune cells to the site of inflammation. Mast cells are present in increased numbers in tissues affected by autoimmune diseases as well as in tumor microenvironments in colorectal, gastric, and pancreatic cancers. Mast cells can suppress immune responses via the expression of checkpoint inhibitor ligands and the release anti-inflammatory cytokines as well as promote vascularization at sites of solid tumors. As a result of these immune regulating activities, mast cells have disease-modifying roles in specific autoimmune diseases and in the development of certain cancers. Therefore, regulating the activities of mast cells in different inflammatory and tumor microenvironments may justify pursuing mast cells and their activities as potential therapeutic targets to treat autoimmune diseases and cancer.